Bacterial community and nitrate removal by simultaneous heterotrophic and autotrophic denitrification in a bioelectrochemically-assisted constructed wetland. (December 2017) - Xu, Dan; Xiao, Enrong; Xu, Peng; Lin, Lili; Zhou, Qiaohong; Xu, Dong; Wu, Zhenbin
Graphical abstract: Highlights: Nitrate was effectively removed in BECW in the presence of organics and current. Heterotrophic and autotrophic denitrifiers resulted in efficient nitrate removal. Cathodic microbial communities in GAC and GF were compared. Pseudomonas and Thiobacillus were predominant in sample GACc and GFc, respectively. Abstract: To enhance nitrate removal in constructed wetlands (CWs), a bioelectrochemically-assisted CW (BECW) integrating a three-dimensional biofilm-electrode reactor (3D-BER) into the CW was evaluated for the effectiveness of combined autotrophic and heterotrophic denitrification in the presence of organic matter and applied current. The effects of COD/N ratios on nitrate removal were investigated, and the bacterial communities in the granular active carbon (GAC) and graphite felt (GF) in the reactor's cathode region were compared. The highest NO3 − -N and TN removal efficiencies of 91.3 ± 7.2% and 68.8 ± 7.9% were obtained at the COD/N ratio of 5. According to the results of high-throughput sequencing analysis, sample GAC was enriched with a high abundance of Pseudomonas (17.29%) capable of autotrophic and heterotrophic denitrification, whereas autotrophic bacteria Thiobacillus (43.94%) was predominant in sample GF. The synergy between heterotrophic and autotrophic denitrification bacteria is believed to cause the high and stable nitrogen removal performance.